2021
DOI: 10.3390/biomedicines9091210
|View full text |Cite
|
Sign up to set email alerts
|

Serum Perilipin 2 (PLIN2) Predicts Multiple Organ Dysfunction in Critically Ill Patients

Abstract: Perilipin 2 (PLIN2) is a lipid droplet protein with various metabolic functions. However, studies investigating PLIN2 in the context of inflammation, especially in systemic and acute inflammation, are lacking. Hence, we assessed the relevance of serum PLIN2 in critically ill patients. We measured serum PLIN2 serum in 259 critically ill patients (166 with sepsis) upon admission to a medical intensive care unit (ICU) compared to 12 healthy controls. A subset of 36 patients underwent computed tomography to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…In contrast, a study that measured PLIN2 serum levels in 259 critically ill patients found no correlation with obesity, body mass index, total cholesterol, triglycerides, diabetes mellitus, traditional markers of inflammation, such as white blood count and C‐reactive protein. However, it did find a strong negative correlation with lipase and adiponectin as well as increased levels in patients with malignant diseases 45 . This suggests that the health status of individuals may significantly impact the quantities of circulating PLIN2, regardless of the typical markers found in obese individuals or patients with diabetes.…”
Section: Overview Of Perlipinsmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, a study that measured PLIN2 serum levels in 259 critically ill patients found no correlation with obesity, body mass index, total cholesterol, triglycerides, diabetes mellitus, traditional markers of inflammation, such as white blood count and C‐reactive protein. However, it did find a strong negative correlation with lipase and adiponectin as well as increased levels in patients with malignant diseases 45 . This suggests that the health status of individuals may significantly impact the quantities of circulating PLIN2, regardless of the typical markers found in obese individuals or patients with diabetes.…”
Section: Overview Of Perlipinsmentioning
confidence: 90%
“…However, it did find a strong negative correlation with lipase and adiponectin as well as increased levels in patients with malignant diseases. 45 This suggests that the health status of individuals may significantly impact the quantities of circulating PLIN2, regardless of the typical markers found in obese individuals or patients with diabetes.…”
Section: Plin2mentioning
confidence: 99%
“…PLIN2 intrinsically acts as a perilipin protein, and its expression and phosphorylation are involved in lipolysis, lipid droplet fusion, and signal transduction ( Kaushik and Cuervo, 2015 ; Kaushik and Cuervo, 2016 ). Elevated serum PLIN2 levels have been observed in response to various inflammatory stimuli, including the production of ROS and inflammatory cytokines ( Marschallinger et al, 2020 ; Kurt et al, 2021 ; Zhang et al, 2021 ). CNBP has been identified as a regulator of NF-kB-dependent proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In different studies, CAVIN3, perilipin 2 (PLIN2), pyruvate dehydrogenase kinase 3 (PDK3), lactate dehydrogenase C (LDHC), and E3 ubiquitin-protein ligase 2 (SIAH2) have been reported to be associated with the occurrence and development of various tumors and poor patient prognosis [32][33][34][35][36]. These markers are expected to be used as markers for targeted tumor therapy and prognostic evaluation.…”
Section: Discussionmentioning
confidence: 99%